Present knowledge review on the problem of leptospirosis - Melnik, O. A. (Journal of Education, Health and Sport, 2019)
The article presented contains meta-analysis of the published data on the problem of leptospirosis, mainly its epidemiology. The problems of taxonomic and genetic classifications are studied, breadth of extension in the world’s different regions analyzed, the relation between leptospirosis causative agents and its hosts is pointed, modern methods of leptospirosis diagnostics are compared. Poor knowledge about the pathology under study has been revealed. The latter is connected with leptospirosis’ neglect, lack or just few governmental initiatives on this problem decision, lack of medical and sanitary guidance.